Interspecies metabolic diversity of harmaline and harmine in in vitro 11 mammalian liver microsomes. Issue 5 (5th July 2016) - Li, Shuping; Teng, Liang; Liu, Wei; Cheng, Xuemei; Jiang, Bo; Wang, Zhengtao; Wang, Changhong
Abstract : The β‐carboline alkaloids harmaline and harmine are widely present in hallucinogenic plants with great potential for treating depression, Parkinson's disease, and Alzheimer's disease. The present study was to elucidate metabolic difference of harmaline and harmine in 11 mammalian liver microsomes in order to quantitate species‐specific metabolic profiles. Using the probe substrate reaction, the enzymatic activities for 8 CYP450 isozymes of 11 liver microsomes were characterized. Combining ultra performance liquid chromatography combined with electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry (UPLC‐ESI‐Q/TOF‐MS) and ultra performance liquid chromatography combined with electrospray ionization quadrupole tandem mass spectrometry (UPLC‐ESI‐MS/MS) methods, 18 metabolites for harmaline and 11 for harmine were identified. The metabolism patterns differences of them presented discrepancy in the quality and quantity of metabolites. It was notable that O ‐sulfate conjugation was detected in all species except sheep. The intrinsic clearance CL int, LM values for the metabolites harmine and harmol in rabbits (37.5 and 42.4 μL/min/mg) were higher than those in other animals, while dogs (16.2 and 16.7 μL/min/mg) and humans (16.0 and 16.3 μL/min/mg) exhibited similar in vitro metabolic clearance. These observations suggested that harmaline and harmine were rapidly metabolized in liver microsomes of rat, mouse, and rabbit; moderately metabolized in human and dog; while weakly metabolized in sheep. Comprehensive analysis of the metabolism indicated that dogs and humans showed considerable similarity in the elimination of parent drugs, metabolic profiles, and catalytic processes. To summarize, these findings illustrated that in vitro studies of harmaline and harmine metabolic profiles in different species are helpful for the proper selection and interpretation of animal models for pharmacological and toxicological evaluation, and will ultimately provide useful guidance for the development of β‐carboline alkaloids. Copyright © 2016 John Wiley & Sons Ltd. Abstract : The study investigates the in vitro species‐specific metabolic profiles of harmaline and harmine in 11 mammalian liver microsomes. Eight CYP450 isozymes from 11 mammalian liver microsomes were characterized. Interspecies metabolic pattern of harmaline and harmine showed obvious discrepancy. Comprehensive analysis indicated dog may be a corking animal model closed to human. Interspecies metabolism play an important role on pharmaco/toxicological evaluation.